Performance evaluation of WT connections in progressive collapse. (15th July 2018) - Daneshvar, Hossein; Driver, Robert G.
Highlights: Detailed finite element analyses of WT connections are performed and results are verified. Rotational capacity of the WT connections in progressive collapse is studied. Failure modes and behaviour of the WT connections in progressive collapse are investigated. New equations are proposed to predict the rotational capacity of the WT connections. The shear-axial-moment interaction curves for the WT connections are developed and discussed. Abstract: In conventional design, shear connections are generally assumed to resist no significant moment or tension. However, since current progressive collapse design guidelines ask engineers to design robust connections that maintain their integrity in a double-span "column removal" scenario, it is important to investigate anticipated shear connection performance under this specific type of loading. There are several types of simple shear connection used in steel structures. WT connections are one relatively common option, but there is limited information about how they would perform under these conditions. In this research, the results of a numerical study conducted to characterize the performance of WT connections under combined shear, moment, and tension are presented. The results are verified with available experimental data. Finite element models consist of a central column stub connected to adjacent beams. The WT connections are modelled as being bolted to both the column flange and beam web. The central stub column is pushed down, while the connection demand and performance are monitored at each stage. It is observed that the tension and moment that develop interact with the shear in the load transfer mechanism. Important aspects of the mode of failure are distinguished and compared with existing test data. Based on the results of this study, models are proposed for WT connections in the column removal scenario. An extensive parametric study is performed in order to investigate the effects of different design parameters, such as WT geometric properties, bolt size and type, and also connection depth. Finally, an equation, based on the connection depth, is proposed to predict the rotational ductility of this connection type when an adjacent column is removed. This study will help to shed lights on the behaviour of WT connections in the column loss event.